UNIPOLAR VERSUS BIPOLAR UNCEMENTED MODULAR HEMIARTHROPLASTY IN PATIENTS WITH DISPLACED FEMORAL NECK FRACTURES: A THREE YEAR FOLLOW-UP - Jain, Vikas; Kamath, Surendra U; Tejaswi, Purnachandra; Hegde, Atmananda S (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Fractures of neck of femur are common fractures in the elderly. To keep up an imperative distance from the poor results of internal fixation and early ambulation of patients, hemiarthroplasty is performed. There is a lacking evidence to bolster the choice between unipolar or bipolar hemiarthroplasty, let alone the modularity of modern components. The objective of this study was to assess and look at the consequences of modern unipolar and the modern bipolar prosthesis in terms of clinical outcome. Methods: This was an observational study comprising 39 patients above 60 years of age with fracture of the femoral neck. Patients were distributed randomly to surgical treatment by either unipolar or bipolar hemiarthroplasty, using modular components, in the department, between December 2013 and September 2015. Outcome was assessed and analyzed primarily using Harris hip score (HHS) and radiological parameters with a follow-up of 6 months. Results: The mean HHS at 6 months in bipolar and unipolar divisions was 75.82±2.37 and 77.00±2.59 points. Range of movement median was 175° and 166° with bipolar and unipolar groups, respectively. Weight bearing mobilization and daily activities were earlier in the bipolar unit. Complications such as prosthesis dislocation were experienced in the modular bipolar unit compared to high-grade infection with the modular unipolar unit. Conclusion: Both groups of patients were associated with comparative mean HHSs. There were no additional clinical or functional advantages for either prosthesis. The complications were limited in both groups. Our outcomes are in coincidence with previously done studies using cemented prostheses. Keywords: Hemiarthroplasty, Modular, Modern, Uncemented, Femur neck, Orthopedic surgery.